2017
DOI: 10.5114/dr.2017.66219
|View full text |Cite
|
Sign up to set email alerts
|

Drug hypersensitivity reactions and allergy in patients with mastocytosis

Abstract: StreSzczenieMastocytoza jest rzadką chorobą szpiku charakteryzującą się nadmierną proliferacją i gromadzeniem się mastocytów w skórze i narządach wewnętrznych. U dzieci najczęstsza jest skórna postać tej choroby. Postać układowa pojawia się przede wszystkim u dorosłych. U chorych na mastocytozę, zarówno skórną, jak i układową, mogą występować objawy zależne od mediatorów uwalnianych przez mastocyty, takie jak: świąd skóry, flushing, hipotensja, bóle brzucha, biegunki, bóle głowy oraz reakcje anafilaktyczne. Sz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Nevertheless, mastocytosis patients require prophylactic antimediator therapy (PAT) and adequate anesthetic management. The PAT is based on H1/H2 antihistamines, glucocorticoids and benzodiazepines given 1 h before the anesthesia [33, 38]. It is suggested to avoid morphine and codeine [39, 40], thiopental [40], succinylcholine [40], mivacurium [40, 41], atracurium [40, 41], rocuronium [40], nefopam [41].…”
Section: Prevention Of the Anaphylaxismentioning
confidence: 99%
“…Nevertheless, mastocytosis patients require prophylactic antimediator therapy (PAT) and adequate anesthetic management. The PAT is based on H1/H2 antihistamines, glucocorticoids and benzodiazepines given 1 h before the anesthesia [33, 38]. It is suggested to avoid morphine and codeine [39, 40], thiopental [40], succinylcholine [40], mivacurium [40, 41], atracurium [40, 41], rocuronium [40], nefopam [41].…”
Section: Prevention Of the Anaphylaxismentioning
confidence: 99%
“…However, this approach might lead to deprivation of proper perioperative analgesia or even needed surgical treatment for SM patients. Furthermore, some authors suggested that severe pain that is not relieved with proper opioid treatment might also cause MC activation [61,62]. Carter et al reported that the risk of anaphylaxis may be significantly greater in major surgeries, patients with anaphylaxis history and in patients not receiving anti-mediator therapy including histamine receptor (HR)1-targeting and HR2-targeting drug [53].…”
Section: General Anestheticsmentioning
confidence: 99%